Sistem Informasi Geografis Dengan Algoritma Dijkstra Untuk Menentukan Jarak Terdekat Pariwisata Di Kabupaten Pesawaran - Pamungkas, Aji; Susanto, Erliyan Redi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Tourism plays an important role in the development of a region. Apart from introducing the area to a wider audience, tourism is also a major source of creating jobs and encouraging local economic growth. Pesawaran Regency, which was previously part of South Lampung Regency, is now a newly formed region. Its location close to Bandar Lampung City, the capital of Lampung Province, provides strategic value that can accelerate the development of the region. Distance problems and uncertainty in finding routes often become obstacles for many people when visiting various locations. Pesawaran Regency has a number of interesting tourist destinations, one of which is Pahawang Island, which is one of the leading tourist destinations. To make it easier for tourists, both local and international, the fastest route to these tourist destinations is needed. This research uses the Dijkstra algorithm to calculate the shortest distance from one point to the selected tourist destination in Pesawaran Regency. This article will review the application of the Dijkstra algorithm in finding the most efficient route for searching tourist locations in Pesawaran Regency. The research results show that this system can help tourists reach tourist locations more quickly.